ESTUDO QUÍMICO DO ÓLEO ESSENCIAL DA Nectandr mebranacea (SW.) Griseb (Lauraceae) DO SUL DE MATO GROSSO DO SUL. - SILVA, V. S.; SILVA, R. C. L.; SILVA, J. C. M.; COSTA, E. R.; LOURO, G. M.; SANTOS, E. O. (ANAIS DO ENIC, 2016)
-